Nanoporous thermal insulation board and preparation method thereof
By combining modified polypropylene fiber with magnesium aluminum silicate and ceramic fiber, the problems of high water absorption and insufficient heat resistance of nano-microporous insulation plate materials are solved, and higher heat resistance, flame retardancy and strength are achieved , suitable for applications in high-heat environments.
Patent Information
- Application Number
- CN202411379741.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Traditional nano microporous thermal insulation plate materials have problems such as high water absorption, poor strength and flammability, especially the lack of heat resistance and flame retardancy of polypropylene fibers, which is difficult to meet the application needs of high-heat environments.
Modified polypropylene fibers are used to improve the compatibility and heat resistance of the fibers by grafting polyphosphamide, trifluoromethyl and polysilicon chains, and are combined with magnesium aluminum silicate and ceramics in nano-microporous insulation plates. The fibers are mixed to form high-performance insulation boards.
It significantly reduces the water absorption rate of nano-microporous insulating plates, improves its heat resistance, flame retardancy and strength, and ensures good insulation performance in high-heat environments.
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, and in particular to a nano-microporous thermal insulation board and a preparation method thereof. Background Art
[0002] Traditional insulating refractory materials include lightweight bricks, lightweight castables and ceramic fibers, but their thermal conductivity is relatively high and cannot meet the current requirements for low thermal conductivity of insulating refractory materials. Nanoporous insulation board is a type of nanoporous insulation material. It is a new type of insulating refractory material. It contains a large number of nano-scale pores. Its thermal conductivity at room temperature is lower than that of still air. It has excellent insulation performance and is widely used in the construction field. The patent with publication number CN110981456A discloses a nanoporous insulation board and its preparation method. The invention introduces organic fibers, and the organic fibers are evenly distributed in the board, so that the integrity of the nano-insulating board is enhanced. However, there are still the following shortcomings: (1) The fumed silica used has a certain water absorption, which increases the water absorption rate of the nanoporous board, resulting in poor strength of the insulation board; (2) The polyethylene fiber in the organic fiber used does not have polar groups in the molecular chain, and has poor compatibility with other inorganic fillers such as fumed silica.
[0003] Polypropylene fiber is one of the commonly used organic reinforcing fibers, but it is flammable and does not have flame retardant properties in its molecular chain. In addition, polypropylene fiber has poor heat resistance and does not meet the use requirements of the high-temperature environment in which nanoporous insulation panels are located. Therefore, a suitable modification method is needed to improve the comprehensive performance of polypropylene fiber and expand its application range. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a nano-microporous insulation board and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A nano-microporous thermal insulation board comprises the following raw materials in parts by weight: 70-80 parts of magnesium aluminum silicate, 15-25 parts of infrared sunscreen, 2-4 parts of ceramic fiber, and 1-3 parts of modified polypropylene fiber;
[0007] The particle size of the magnesium aluminum silicate is 325 mesh; the infrared sunscreen is silicon carbide with a particle size of 3-5 μm; the diameter of the ceramic fiber is 3-5 μm;
[0008] The preparation of the nanoporous thermal insulation board comprises the following steps:
[0009] Aluminum magnesium silicate, infrared shading agent, ceramic fiber and modified polypropylene fiber are added to a reaction kettle and stirred for 20-30 minutes to obtain a mixture. The mixture is then put into a grinder and ground for 1-1.5 hours. The mixture is then transferred to a mixer and mixed at 150-170°C for 40-50 minutes. The mixed mixture is then loaded into an elastic mold and sealed. The sealed elastic mold is placed in a pressurized container at 200-220MPa and pressurized for 4-6 minutes to obtain a nanoporous insulation board.
[0010] The modified polypropylene fiber is prepared by the following steps:
[0011] Step A1: Add 1-(4-nitro-2-trifluoromethylphenyl)-piperazine into a three-necked flask, start stirring, then add chloroform, place the three-necked flask in an ice bath at 0°C, slowly add allylphosphine dichloride, continue stirring to react for 4-5 h, then filter, wash with chloroform, and rotary evaporate to obtain reaction product 1;
[0012] Further, the usage ratio of 1-(4-nitro-2-trifluoromethylphenyl)-piperazine, chloroform, and allylphosphine dichloride is 0.63 mol:430-450 mL:0.2 mol;
[0013] During the reaction of step A1, the secondary amine group in 1-(4-nitro-2-trifluoromethylphenyl)-piperazine reacts with phosphorus oxychloride of allylphosphine dichloride to generate reaction product 1;
[0014] Step A2: Add the reaction product 1 and toluene into a three-necked flask, heat to 45-55°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1-1.5h to obtain the reaction product 2;
[0015] Further, the usage ratio of the reaction product 1, toluene and sodium dithionite is 0.1 mol: 150-160 mL: 0.2-0.25 mol;
[0016] During the reaction of step A2, the nitro group of the reaction product 1 is reduced to an amino group, thereby obtaining a reaction product 2 containing an amino group;
[0017] Step A3: Add 3-chloropropylpentamethyldisiloxane and the reaction product 2 to methanol, then add sodium bisulfate, start stirring, react at 50-60° C. for 8-10 hours, filter, extract, and dry to obtain a functional monomer;
[0018] Further, the usage ratio of 3-chloropropylpentamethyldisiloxane, reaction product 2, methanol and sodium bisulfate is 0.4 mol: 0.1 mol: 320-330 mL: 0.0040-0.0045 g;
[0019] During the reaction of step A3, sodium bisulfate catalyzes the dehydrochlorination of 3-chloropropylpentamethyldisiloxane and the reaction product 2 to generate a functional monomer;
[0020] Step A4: In a nitrogen atmosphere, toluene, functional monomers and crosslinking agents were added to the reaction bottle, stirred for 10-15 minutes, polypropylene fibers were added and stirred for 10-15 minutes, and the reaction bottle was sealed and then 60 After irradiation with Coγ-rays for 8-10 hours, the polypropylene fibers are taken out, washed with anhydrous ethanol, extracted with acetone, and dried to obtain modified polypropylene fibers;
[0021] Further, the usage ratio of toluene, functional monomer, crosslinking agent and polypropylene fiber is 400-450 mL: 10-15 g: 7-9 g: 100-110 g;
[0022] During the reaction of step A4, 60 Under the irradiation of Coγ-rays and the assistance of a cross-linking agent, the functional monomers are grafted onto the polypropylene fibers to obtain modified polypropylene fibers.
[0023] Beneficial effects of the invention: The invention discloses a nano-microporous thermal insulation board, comprising the following raw materials: magnesium aluminum silicate, infrared sunscreen, ceramic fiber and modified polypropylene fiber. The magnesium aluminum silicate used has a high specific surface area and a lower water absorption rate than fumed silica, thus meeting the requirement of the nano-microporous thermal insulation board for low water absorption rate.
[0024] During the grinding stage of the preparation process of the nanoporous insulation board, the modified polypropylene fiber is mixed with a powdered mixture of magnesium aluminum silicate, silicon carbide, and ceramic fiber; during the heating and mixing process, the modified polypropylene fiber changes from a solid state to a molten state; after cooling, it adheres to the powdered mixture of magnesium aluminum silicate, silicon carbide, and ceramic fiber to enhance the integrity of the nanoporous insulation board. The synthesized modified polypropylene fiber is obtained by grafting functional monomers with polypropylene fibers. Polyphosphoramide, trifluoromethyl, and polysiloxane chains are introduced into the polypropylene fibers. Compared with polypropylene fibers, the modified polypropylene fibers have a certain polarity and increased compatibility with magnesium aluminum silicate, silicon carbide, and ceramic fibers; the Si-O-Si bond and Si-C bond contained in the polysiloxane chain have high bond energies and high energy required for breaking, which enhances the thermal stability of the polypropylene fiber and improves the heat resistance of the nanoporous insulation board. When the nanoporous insulation board is in a high-heat environment, it can still maintain good thermal insulation and heat preservation properties; polyphosphoramide has the characteristics of expansion and flame retardancy, and can form a sufficiently dense surface during combustion. A protective honeycomb carbon layer with a sufficiently large expansion multiple and high strength is coated on the surface of the substrate, acting as a heat-insulating and oxygen-isolating barrier to prevent combustion; trifluoromethyl has strong hydrophobicity, which enhances the waterproofness of the nanoporous insulation board, further reduces the water absorption rate of the nanoporous insulation board, and improves the surface hardness, thereby enhancing the strength of the nanoporous insulation board; the present invention grafts functional monomers containing polysiloxane chains, polyphosphoramide and trifluoromethyl onto modified polypropylene fibers through a series of chemical reactions, and as the powdery mixture formed by the modified polypropylene fibers and other raw materials is evenly mixed and adhered, the dispersion in the matrix is increased, thereby improving the heat resistance, flame retardancy and strength of the nanoporous insulation board. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Embodiment 1: A modified polypropylene fiber, the preparation of which comprises the following steps:
[0027] Step A1: Add 1-(4-nitro-2-trifluoromethylphenyl)-piperazine to a three-necked flask, start stirring, then add chloroform, place the three-necked flask in an ice bath pot at 0°C, slowly add allyl phosphine dichloride, continue stirring to react for 4 hours, then filter, wash with chloroform, and rotary evaporate to obtain reaction product 1; the dosage ratio of 1-(4-nitro-2-trifluoromethylphenyl)-piperazine, chloroform, and allyl phosphine dichloride is 0.63 mol:430 mL:0.2 mol;
[0028] Step A2: Add the reaction product 1 and toluene into a three-necked flask, heat to 45°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1 hour to obtain the reaction product 2; the amount ratio of the reaction product 1, toluene and sodium dithionite is 0.1 mol: 100 mL: 0.2 mol;
[0029] Step A3: Add 3-chloropropylpentamethyldisiloxane and reaction product 2 to methanol, then add sodium bisulfate, start stirring, react at 50° C. for 8 hours, filter, extract, and dry to obtain a functional monomer; the amount ratio of 3-chloropropylpentamethyldisiloxane, reaction product 2, methanol, and sodium bisulfate is 0.4 mol: 0.1 mol: 320 mL: 0.0040 g;
[0030] Step A4: In a nitrogen atmosphere, toluene, functional monomers and crosslinking agents were added to the reaction bottle, stirred for 10 min, polypropylene fibers were added and stirred for another 10 min, the reaction bottle was sealed, and then 60 After 8 hours of Coγ-ray irradiation, the fiber was taken out and rinsed with anhydrous ethanol, extracted with acetone and dried to obtain modified polypropylene fiber; the dosage ratio of toluene, functional monomer, crosslinking agent and polypropylene fiber was 400mL:10g:7g:100g.
[0031] Embodiment 2: A modified polypropylene fiber, the preparation of which comprises the following steps:
[0032] Step A1: Add 1-(4-nitro-2-trifluoromethylphenyl)-piperazine to a three-necked flask, start stirring, then add chloroform, place the three-necked flask in an ice bath at 0°C, slowly add allyl phosphine dichloride, continue stirring to react for 4.5 h, then filter, wash with chloroform, and rotary evaporate to obtain reaction product 1; the dosage ratio of 1-(4-nitro-2-trifluoromethylphenyl)-piperazine, chloroform, and allyl phosphine dichloride is 0.63 mol:440 mL:0.2 mol;
[0033] Step A2: Add the reaction product 1 and toluene into a three-necked flask, heat to 50°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1.3h to obtain the reaction product 2; the amount ratio of the reaction product 1, toluene and sodium dithionite is 0.1mol:105mL:0.23mol;
[0034] Step A3: Add 3-chloropropylpentamethyldisiloxane and reaction product 2 to methanol, then add sodium bisulfate, start stirring, react at 55° C. for 9 hours, filter, extract, and dry to obtain a functional monomer; the amount ratio of 3-chloropropylpentamethyldisiloxane, reaction product 2, methanol, and sodium bisulfate is 0.4 mol: 0.1 mol: 325 mL: 0.0043 g;
[0035] Step A4: In a nitrogen atmosphere, toluene, functional monomers and crosslinking agents were added to the reaction bottle, stirred for 13 minutes, polypropylene fibers were added and stirred for another 13 minutes, the reaction bottle was sealed, and then 60 After irradiation with Coγ rays for 9 hours, the fiber was taken out and rinsed with anhydrous ethanol, extracted with acetone and dried to obtain modified polypropylene fiber; the dosage ratio of toluene, functional monomer, crosslinking agent and polypropylene fiber was 425mL:13g:8g:105g.
[0036] Embodiment 3: A modified polypropylene fiber, the preparation of which comprises the following steps:
[0037] Step A1: Add 1-(4-nitro-2-trifluoromethylphenyl)-piperazine into a three-necked flask, start stirring, then add chloroform, place the three-necked flask in an ice bath pot at 0°C, slowly add allyl phosphine dichloride, continue stirring to react for 5 hours, then filter, wash with chloroform, and rotary evaporate to obtain reaction product 1; the dosage ratio of 1-(4-nitro-2-trifluoromethylphenyl)-piperazine, chloroform, and allyl phosphine dichloride is 0.63 mol:450 mL:0.2 mol;
[0038] Step A2: Add the reaction product 1 and toluene into a three-necked flask, heat to 55°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1.5 hours to obtain the reaction product 2; the amount ratio of the reaction product 1, toluene and sodium dithionite is 0.1 mol: 110 mL: 0.25 mol;
[0039] Step A3: Add 3-chloropropylpentamethyldisiloxane and reaction product 2 to methanol, then add sodium bisulfate, start stirring, react at 60° C. for 10 hours, filter, extract, and dry to obtain a functional monomer; the amount ratio of 3-chloropropylpentamethyldisiloxane, reaction product 2, methanol, and sodium bisulfate is 0.4 mol: 0.1 mol: 330 mL: 0.0045 g;
[0040] Step A4: In a nitrogen atmosphere, toluene, functional monomers and crosslinking agents were added to the reaction bottle, stirred for 15 min, polypropylene fibers were added and stirred for another 15 min, the reaction bottle was sealed, and then 60 After 10 hours of Coγ-ray irradiation, the fiber was taken out and rinsed with anhydrous ethanol, extracted with acetone and dried to obtain modified polypropylene fiber; the dosage ratio of toluene, functional monomer, crosslinking agent and polypropylene fiber was 450mL:15g:9g:110g.
[0041] Embodiment 4: A nanoporous thermal insulation board comprises the following raw materials in parts by weight: 70 parts of magnesium aluminum silicate, 25 parts of infrared sunscreen, 2 parts of ceramic fiber, and 3 parts of modified polypropylene fiber; the particle size of the magnesium aluminum silicate is 325 mesh; the infrared sunscreen is silicon carbide with a particle size of 3 μm; the diameter of the ceramic fiber is 3 μm;
[0042] The preparation of the nanoporous thermal insulation board comprises the following steps:
[0043] Aluminum magnesium silicate, infrared shading agent, ceramic fiber and modified polypropylene fiber obtained in Example 1 are added to a reactor and stirred for 20 minutes to obtain a mixture. The mixture is then put into a grinder and ground for 1 hour. The mixture is then transferred to a mixer and mixed at 150°C for 40 minutes. The mixed mixture is then loaded into an elastic mold and sealed. The sealed elastic mold is placed in a pressurized container at 200 MPa and pressurized for 4 minutes to obtain a nanoporous insulation board.
[0044] Embodiment 5: A nanoporous thermal insulation board comprises the following raw materials in parts by weight: 75 parts of magnesium aluminum silicate, 20 parts of infrared sunscreen, 3 parts of ceramic fiber, and 2 parts of modified polypropylene fiber; the particle size of the magnesium aluminum silicate is 325 mesh; the infrared sunscreen is silicon carbide with a particle size of 4 μm; the diameter of the ceramic fiber is 4 μm;
[0045] The preparation of the nanoporous thermal insulation board comprises the following steps:
[0046] Aluminum magnesium silicate, infrared shading agent, ceramic fiber and modified polypropylene fiber obtained in Example 2 were added to a reactor and stirred for 25 minutes to obtain a mixture. The mixture was then put into a grinder and ground for 1.3 hours. The mixture was then transferred to a mixer and mixed at 160°C for 45 minutes. The mixed mixture was then loaded into an elastic mold and sealed. The sealed elastic mold was placed in a pressurized container at 210 MPa and pressurized for 5 minutes to obtain a nanoporous insulation board.
[0047] Embodiment 6: A nanoporous thermal insulation board comprises the following raw materials in parts by weight: 80 parts of magnesium aluminum silicate, 15 parts of infrared sunscreen, 4 parts of ceramic fiber, and 1 part of modified polypropylene fiber; the particle size of the magnesium aluminum silicate is 325 mesh; the infrared sunscreen is silicon carbide with a particle size of 5 μm; the diameter of the ceramic fiber is 5 μm;
[0048] The preparation of the nanoporous thermal insulation board comprises the following steps:
[0049] Aluminum magnesium silicate, infrared shading agent, ceramic fiber and modified polypropylene fiber obtained in Example 3 are added to a reactor and stirred for 30 minutes to obtain a mixture. The mixture is then put into a grinder and ground for 1.5 hours. The mixture is then transferred to a mixer and mixed at 170°C for 50 minutes. The mixed mixture is then loaded into an elastic mold and sealed. The sealed elastic mold is placed in a pressurized container at 220 MPa and pressurized for 6 minutes to obtain a nanoporous insulation board.
[0050] Comparative Example 1: Compared with Example 6, the modified polypropylene fiber is replaced with ordinary polypropylene fiber, and the rest is exactly the same as Example 6 to prepare a nano-microporous insulation board.
[0051] Comparative Example 2: Compared with Example 6, the functional monomer used in the preparation of the modified polypropylene fiber in Example 3 is replaced by the reaction product 1 in Example 3, that is, no polysiloxane chain is introduced, and the rest is exactly the same as Example 6 to obtain a nanoporous insulation board.
[0052] The nano-microporous thermal insulation board disclosed in the present invention is further tested for its effect, and the test results are as follows.
[0053] In order to test the nanoporous insulation board disclosed in the present invention, the compressive strength was measured according to GB / T13480-2014 "Determination of compression properties of thermal insulation products for building use"; the flame retardant performance was measured according to GB8624-2012 "Classification of combustion performance of building materials and products"; the heating line shrinkage was measured with reference to GB / T17911-2018 "Test methods for refractory fiber products", and the results are recorded in Table 1;
[0054] Table 1: Test results
[0055] Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Compressive strength (MPa) 0.92 0.95 0.97 0.75 0.95 Combustion level A-level A-level A-level B1 A-level Heating wire shrinkage at 1000℃ (%) 1.75 1.78 1.85 2.69 2.56
[0056] According to the data in Table 1, the nanoporous insulation board prepared by the present invention has good heat resistance, strength and flame retardancy; by comparing Example 6 with Comparative Example 1, it can be seen that the use of modified polypropylene fiber, the introduction of polysiloxane chains, trifluoromethyl and polyphosphoramide can improve the heat resistance, strength and flame retardancy of the nanoporous insulation board; by comparing Example 6 with Comparative Example 2, it can be seen that the introduction of polysiloxane chains can improve the heat resistance of the nanoporous insulation board.
[0057] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A nanoporous thermal insulation board, Features: The method comprises the following raw materials in parts by weight: 70-80 parts of magnesium aluminum silicate, 15-25 parts of infrared sunscreen agent, 2-4 parts of ceramic fiber, and 1-3 parts of modified polypropylene fiber; The modified polypropylene fiber is prepared by the following steps: Step A1: Add 1-(4-nitro-2-trifluoromethylphenyl)-piperazine into a three-necked flask, start stirring, then add chloroform, place the three-necked flask in an ice bath pot at 0°C, slowly add allylphosphine dichloride, continue stirring to react for 4-5h, then filter, wash with chloroform, and rotary evaporate to obtain reaction product 1; Step A2: Add the reaction product 1 and toluene into a three-necked flask, heat to 45-55°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1-1.5h to obtain the reaction product 2; Step A3: Add 3-chloropropylpentamethyldisiloxane and the reaction product 2 to methanol, then add sodium bisulfate, start stirring, react at 50-60° C. for 8-10 hours, filter, extract, and dry to obtain a functional monomer; Step A4: In a nitrogen atmosphere, toluene, functional monomers and crosslinking agents were added to the reaction bottle, stirred for 10-15 minutes, polypropylene fibers were added and stirred for 10-15 minutes, and the reaction bottle was sealed and then 60 After irradiation with Coγ rays for 8-10 hours, the polypropylene fibers are taken out, rinsed with anhydrous ethanol, extracted with acetone, and dried to obtain modified polypropylene fibers.
2. A nanoporous thermal insulation board according to claim 1, Features: In step A1, the usage ratio of 1-(4-nitro-2-trifluoromethylphenyl)-piperazine, chloroform and allylphosphine dichloride is 0.63 mol:430-450 mL:0.2 mol.
3. A nanoporous thermal insulation board according to claim 1, Features: In step A2, the usage ratio of reaction product 1, toluene and sodium dithionite is 0.1 mol:150-160 mL:0.2-0.25 mol.
4. A nanoporous thermal insulation board according to claim 1, Features: In step A3, the usage ratio of 3-chloropropylpentamethyldisiloxane, reaction product 2, methanol and sodium bisulfate is 0.4 mol: 0.1 mol: 320-330 mL: 0.0040-0.0045 g.
5. The nanoporous thermal insulation board according to claim 1, Features: In step A4, the usage ratio of toluene, functional monomer, cross-linking agent and polypropylene fiber is 400-450 mL: 10-15 g: 7-9 g: 100-110 g.
6. The nanoporous thermal insulation board according to claim 1, Features: The particle size of the magnesium aluminum silicate is 325 meshes; the infrared sunscreen is silicon carbide with a particle size of 3-5 μm; and the diameter of the ceramic fiber is 3-5 μm.
7. The method for preparing a nanoporous thermal insulation board according to claim 1, Features: The steps include: Aluminum magnesium silicate, infrared shading agent, ceramic fiber and modified polypropylene fiber are added to a reaction kettle and stirred for 20-30 minutes to obtain a mixture. The mixture is then put into a grinder and ground for 1-1.5 hours. The mixture is then transferred to a mixer and mixed at 150-170°C for 40-50 minutes. The mixed mixture is then loaded into an elastic mold and sealed. The sealed elastic mold is placed in a pressurized container at 200-220MPa and pressurized for 4-6 minutes to obtain a nanoporous insulation board.
